PENGARUH PERMAINAN KOLASE TERHADAP KEMAMPUAN MOTORIK HALUS ANAK DI KELOMPOK B TK PERTIWI KECAMATAN PALU TIMUR - Midelisna Kadoy; Didik Purwanto; Amrullah; Andi Agusniatih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research identifies issues related to children's fine motor skills that have not developed as expected, based on initial observations. The aim of this study is to evaluate the effect of collage play on children's fine motor skills. The method used is a quantitative approach with an experimental research type, involving 15 children, consisting of 7 boys and 8 girls. The results of initial and final observations indicate an increase in children's fine motor skills after the application of the collage play method. It can be seen from the recap of observations of children's abilities before and after being given collage activities. From the aspect of accuracy in adhering to patterns, in the BSB category, the percentage increased from 0% to 46.67%; in the BSH category, from 13.33% to 26.67%; in the MB category, from 33.33% to 26.67%; and in the BB category, from 53.33% to 0%. Meanwhile, for the second aspect, which is finger strength, in the BSB category, it increased from 0% to 53.33%; in the BSH category, from 6.67% to 20%; in the MB category, from 46.67% to 26.67%; and in the BB category, from 46.67% to 0%. The final aspect is the speed of adhering, where in the BSB category, it increased from 0% to 53.33%; in the BSH category, from 20% to 26.67%; in the MB category, from 33.33% to 20%; and in the BB category, from 46.67% to 0%.